SOME ASPECTS OF ADMINISTRATIVE AND PROCEDURAL LEGAL CAPACITY OF THE SUBJECTS OF EXECUTIVE PROCEEDINGS - L. V. Krupnova (Bulletin of Kharkiv National University of Internal Affairs, 2018)
It has been noted that in the context of reforming the system of executive proceedings in Ukraine, there is the issue of administrative procedural legal capacity of the agencies of compulsory execution and persons exercising delegated authority in this area. Significant changes in the law on executive proceedings, require a comprehensive analysis of the legal status of its subjects, and, in particular, the definition of the content of their administrative procedural legal capacity.Therefore, the subject matter of the study became the essential aspects of administrative procedural legal capacity of the subjects of executive proceedings, and the objective of the article – is to comprehensively study the concept and to characterize the content of administrative procedural legal capacity of the subjects of executive proceedings in Ukraine.The main features of the researched category have been formulated and its author’s definition has been provided. The content of administrative procedural legal capacity of the subjects of executive proceedings and its normative and legal basis have been revealed. It has been established that administrative procedural legal capacity of the subjects of executive proceedings consists in the ability to exercise procedural rights and to perform duties while implementing compulsory execution of jurisdictional decisions. It has been substantiated that administrative procedural legal capacity reflects a volitional aspect in legal relations on compulsory execution of the decisions, because it is connected with actions or omission of the subjects of executive proceedings. The issue of the role of the researched category within functional filling of the legal status of the subjects of executive proceedings has been considered.It has been concluded that administrative procedural legal capacity of the subjects of executive proceedings arises simultaneously with administrative procedural legal ability, provides reality to the latter within the legal field and outlines the limits of the legality of the conduct of the subjects of executive proceedings.